Thermodynamics processes and applications - Logan, Earl (Mechanical engineering (Marcel Dekker, Inc.), 1999)
Provides a solid grounding in the basic principles of the science of thermodynamics proceeding to practical, hands-on applications in large-scale industrial settings. Presents myriad applications for power plants, refrigeration and air conditioning systems, and turbomachinery. Features hundreds of helpful example problems and analytical exercises. Solutions manual is available to instructors.